GAMBARAN PENGELOLAAN KELOMPOK BERMAIN DI TK FKIP UNIVERSITAS RIAU - Daviq Chairilsyah (Jurnal Educhild : Pendidikan dan Sosial, 2018)
This research is to find out how the description of the management of the Play Group (KB) in TKFKIP University of Riau (UR). The research subjects in this study were one KB room in FKIP URwith the number of indicators to be examined as many as 8 indicators and 17 sub-indicatorsused. The method used is quantitative descriptive method to find out the description of familyplanning management. Data collection techniques used are using observation sheets. Basedon the results of data analysis obtained the results of the percentage of 8 indicators, namely: Onthe indicator of the physical arrangement of FP FKIP UR is (87.5%) the KB FKIP UR is said to bevery good (SB). Indicators of toys and KB equipment FKIP UR are (75%) the KB FKIP UR is saidto be good (B). The indicator of the ratio of caregivers of FPIP UR KB children is (75%) the KB FKIPUR is said to be good (B). Indicators of FKIP UR’s KB daily activities are (100%) the FKIP UR KBis said to be very good (SB). The indicator of FPIP UR KB caregiver qualification is (75%) the FKIPUR KB is said to be good (B). Indicators of FKIP UR KB adult interaction are (100%) the FKIP URKB is said to be very good (SB). The indicator of the relationship with the parents of FKIP UR KBis (100%) the KB FKIP UR is said to be very good (SB). The indicator of licensing and KBaccreditation FKIP UR is (87.5%) then in general the FP FP UR management is said to be verygood (SB). Penelitian ini untuk mengetahui bagaimana gambaran pengelolaan Kelompok Bermain (KB) diTK FKIP Universitas Riau (UR). Adapun subjek penelitian dalam penelitian ini adalah satu ruanganKB di FKIP UR dengan jumlah indikator yang akan diteliti sebanyak 8 indikator dan 17 subindikator yang digunakan. Metode yang digunakan yaitu metode deskriptif kuantitatif untukmengetahui gambaran pengelolaan KB tersebut. Teknik pengumpulan data yang digunakanyaitu menggunakan lembar observasi. Berdasarkan hasil analisis data diperoleh hasil persentasedari 8 indikator yaitu: Pada indikator pengaturan fisik KB FKIP UR adalah (87,5%) maka KB FKIPUR sudah dikatakan sangat baik (SB). Indikator mainan dan Peralatan KB FKIP UR adalah(75%) maka KB FKIP UR sudah dikatakan baik (B). Indikator rasio pengasuh anak KB FKIP URadalah (75%) maka KB FKIP UR sudah dikatakan baik (B). Indikator kegiatan sehari-hari KBFKIP UR adalah (100%) maka KB FKIP UR sudah dikatakan sangat baik (SB). Indikator kualifikasipengasuh KB FKIP UR adalah (75%) maka KB FKIP UR sudah dikatakan baik (B). Indikatorinteraksi orang dewasa KB FKIP UR adalah (100%) maka KB FKIP UR sudah dikatakan sangatbaik (SB). Indikator hubungan dengan orang tua KB FKIP UR adalah (100%) maka KB FKIP URsudah dikatakan sangat baik (SB). Indikator perizinan dan akreditasi KB FKIP UR adalah (87,5%)maka secara umum pengelolaan KB FKIP UR sudah dikatakan sangat baik (SB).